2020
DOI: 10.3390/geosciences10020067
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities of Novaya Zemlya Archipelago Ice and Permafrost

Abstract: The study of bacterial communities associated with extreme ecosystems is one of the most important tasks in modern microbial ecology. Despite a large number of studies being performed, the ecosystems that have not been sufficiently explored from the microbiological point of view still exist. Such research is needed for improving the understanding of the limits and mechanisms of bacterial survival under extreme conditions, and for revealing previously undescribed species and their role in global biospheric proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“…The two XDR Paralcaligenes cave strains SC18B.3 (900-years BP) and SC71.3 (7000-years BP) appeared to have an opposite phenotype as their homologs isolated from soil resistant to only lincomycin, oleandomycin, rifampicin, and vancomycin 85 . Other four XDR cave isolates belonging to Flavobacterium, Paralcaligenes, Phenylobacterium and Microbacterium genera isolated from up to 9000-years old ice (Supplementary Table S1 ) revealed a broader AR than the corresponding species from clinical isolates 86 , but also Antarctic 80 and Arctic 9 , 54 cold habitats.…”
Section: Discussionmentioning
confidence: 99%
“…The two XDR Paralcaligenes cave strains SC18B.3 (900-years BP) and SC71.3 (7000-years BP) appeared to have an opposite phenotype as their homologs isolated from soil resistant to only lincomycin, oleandomycin, rifampicin, and vancomycin 85 . Other four XDR cave isolates belonging to Flavobacterium, Paralcaligenes, Phenylobacterium and Microbacterium genera isolated from up to 9000-years old ice (Supplementary Table S1 ) revealed a broader AR than the corresponding species from clinical isolates 86 , but also Antarctic 80 and Arctic 9 , 54 cold habitats.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the mechanism of perchlorate action on microorganisms in soils, it is necessary to carry out parallel incubation and analysis of samples both in the presence of perchlorate and in the presence of other salts, for example, chlorides, which do not possess the properties of strong oxidizers. It is shown that about 30–70% of culturable heterotrophic aerobic bacteria isolated from arid soils and permafrosts are able to grow in media containing 5% NaCl (Belov et al ., 2018, 2019, 2020 a , 2020 b ). It is known that sodium chloride at concentrations ~5% inhibit microbial growth (in terms of [ 3 H]-leucine incorporation into biomass) and respiration in soils at 2–3 times (Wichern et al ., 2006; Rousk et al ., 2011; Rath et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This concentration is not the limit at which the survival of certain microorganisms is indicated. However, this concentration can inhibit the growth and metabolic activity of microorganisms and lead to their death (Matsubara et al ., 2017; Beblo-Vranesevic et al ., 2017 b ; Belov et al ., 2018, 2019, 2020 a , 2020 b ). Thereby, the discovery of such a high tolerance of soil microbial communities is somewhat unexpected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations